2016
DOI: 10.1097/coh.0000000000000259
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C virus coinfection as a risk factor for osteoporosis and fracture

Abstract: Purpose of Review With increased survival of HIV-infected patients, osteoporotic fractures have developed as a major cause of morbidity in these patients, and chronic hepatitis C virus (HCV) co-infection has emerged as a significant contributor to this increased fracture risk. This article reviews the epidemiologic and clinical evidence for osteoporosis and increased fracture risk among HIV/HCV co-infected patients, as well as potential mechanisms for these outcomes with HCV co-infection. Recent Findings Epi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 79 publications
1
14
0
1
Order By: Relevance
“…In Taiwan, there is a high prevalence of hepatitis B and C 2931. In previous studies, hepatitis has been shown to increase the risk of osteoporosis in Taiwan 3234. Thus, patients with hepatitis may be more likely to visit an osteoporosis clinic for low bone mass-related fractures, further strengthening the consideration that hepatitis is an associated medical illness, as noted in this study.…”
Section: Discussionsupporting
confidence: 74%
“…In Taiwan, there is a high prevalence of hepatitis B and C 2931. In previous studies, hepatitis has been shown to increase the risk of osteoporosis in Taiwan 3234. Thus, patients with hepatitis may be more likely to visit an osteoporosis clinic for low bone mass-related fractures, further strengthening the consideration that hepatitis is an associated medical illness, as noted in this study.…”
Section: Discussionsupporting
confidence: 74%
“…Substance abuse, including alcohol and intravenous drug use, is also highly prevalent in PLWH and has been linked to CVD, geriatric syndromes, and increased all-cause mortality (Chander et al, 2006). Co-infections with HBV and HCV, as mentioned previously, lead to a higher burden of hepatocellular carcinoma, and HCV infection is also an independent risk factor for osteopenia and osteoporosis (Bedimo et al, 2016). Other traditional risk factors for the development of chronic diseases, including hypertension, diabetes, dyslipidemia, and obesity, are all seen at increased rates in PLWH.…”
Section: Mechanisms Behind the Increased Burden Of Chronic Illnesses mentioning
confidence: 96%
“…Suboptimal serum vitamin D is frequently observed in HIV/AIDS patients treated with anti-retroviral pharmaceuticals (Mastaglia et al 2017). Epidemiologic studies suggested a three-fold increased fracture incidence in patients coinfected with HIV/hepatitis C virus even before development of cirrhosis (Bedimo et al 2016, Weitzmann et al 2016) (see below).…”
Section: Cirrhosis Of the Liver And/or Chronic Hepatitismentioning
confidence: 99%
“…Complication of cirrhosis with osteoporosis is very common (50 %), in chronic active hepatitis 9.1 % (Bedimo et al 2016). Fractures are often two fold in patients with chronic liver disease (Handzlik-Orlik et al (2016).…”
Section: Cirrhosis Of the Liver And/or Chronic Hepatitismentioning
confidence: 99%